Corporate political activity and MNEs’ sustainability performance: Evidence from sub-Saharan Africa - Adomako, Samuel; Donbesuur, Francis; Nyuur, Richard B.; Apprey, Pius Lord; Abu-Arja, Ahmad (Elsevier, 2026)
This article examines the effect of corporate political activities (CPA) on sustainability performance through the mediating mechanism of political influence. It further investigates the contingent factors influencing the relationship between political influence and corporate sustainability performance. Our hypotheses are largely supported by time-lagged data from 348 multinational enterprises (MNEs) operating in four sub-Saharan African countries. Our findings extend nonmarket strategies (NMS) and sustainability literature by testing a mediating and contingent model that assesses the influence of CPA on corporate sustainability performance. This nuanced analysis broadens the conceptual scope and applicability of NMS and sustainability activities, particularly in non-Western contexts.
Keywords: Nonmarket strategy Corporate sustainability; Equity control; Economic development Developing; economies MNEs; Corporate political activity; fi=InnoLab|en=InnoLab|